Mind-Wandering With and Without Intention. Issue 8 (August 2016) - Seli, Paul; Risko, Evan F.; Smilek, Daniel; Schacter, Daniel L.
Abstract : The past decade has seen a surge of research examining mind-wandering, but most of this research has not considered the potential importance of distinguishing between intentional and unintentional mind-wandering. However, a recent series of papers have demonstrated that mind-wandering reported in empirical investigations frequently occurs with and without intention, and, more crucially, that intentional and unintentional mind-wandering are dissociable. This emerging literature suggests that, to increase clarity in the literature, there is a need to reconsider the bulk of the mind-wandering literature with an eye toward deconvolving these two different cognitive experiences. In this review we highlight recent trends in investigations of the intentionality of mind-wandering, and we outline a novel theoretical framework regarding the mechanisms underlying intentional and unintentional mind-wandering. Trends: Researchers are beginning to recognize the importance of distinguishing between intentional and unintentional forms of mind-wandering. The standard practice has been to employ dichotomous probes that ask people to report whether they are 'on task' or 'mind-wandering', which conflates intentional and unintentional types of mind-wandering. A growing number of studies have shown that people intentionally mind-wander both in laboratory tasks and in everyday life, and that intentional and unintentional mind-wandering are dissociable cognitive experiences. Extant theories have largely neglected the distinction between unintentional and intentional mind-wandering, and must be amended to include the important role of intentionality.